Self-powered triboelectric nanogenerator driven nanowires electrode array system for the urine sterilization. (1st June 2022) - Zhang, Xinmeng; Huang, Haoqiang; Zhang, Weinan; Hu, Zulu; Li, Xiang; Liu, Jia; Xu, Gaixia; Yang, Chengbin
Abstract: Urine is the primary source of pathogens (viruses, fungi, and bacteria) in urban sewage. The epidemic spread of these pathogens has a severe threat to human health and the ecological environment. The traditional sewage sterilization methods usually produce harmful by-products and have high energy consumption. These weaknesses restrict the quality of the purified water and economic benefits. Herein, we elaborately fabricated a triboelectric nanogenerator driving nanowires electrode array (T-NEA) system for removing bacteria in the urine. An irreversible electroporation damage results in high-efficiency bacteria inactivation. The sterilization efficiency of T-NEA system is more than 99.9999% in artificial urine contaminated by Escherichia coli ( E. coli ), Staphylococcus aureus ( S. aureus ) and Klebsiella pneumoniae (K. pneumoniae), Pseudomonas aeruginosa (P. aeruginosa) . Those bacteria could cause epidemic infection in hospital. The electroporation effect on the bacterial membrane was confirmed by SEM imaging and confocal laser scanning microscopy. In addition, it was demonstrated that the radical oxygen species accompanied by T-NEA working could degrade the organic components in artificial urine. After being treated by T-NEA for 30 mins, the reduction rates of the total organic carbon and total nitrogen in the artificial urine reached up to 30.41% and 33.79%. Meanwhile, the degradation degree of urea, uric acid, and creatinine reached 37.39%, 30.50%, 6.25%, respectively. And the degradation mechanism of organic materials in urine was also investigated. This work provided an effective self-powered system which could totally remove the hazardous bacteria and degrade the organics in the urine. Graphical Abstract: ga1 Highlights: A self-powered triboelectric nanogenerator driven nanowires electrode array sterilization system was firstly constructed. This T-NEA system present excellent bacteria removal efficiency and organics degradation ability. The mechanism of T-NEA sterilization system based on irreversible electroporation was demonstrated.